Peluang DOAJ Sebagai Alternatif Open Educational Resources di Masa Pandemi Covid-19 - Khabibul Umam; Thoriq Tri Prabowo (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2022)
Purpose. This study aims to describe the potential of DOAJ as an alternative to open source learning during a pandemic.Method. The method used in this research is the literature study.Result and discussion. Based on the literature search, DOAJ's potential as OER during the pandemic can be seen based on the characteristics of DOAJ which are digital, online, free, and free of copyright and licensing restrictions. This study concludes that DOAJ has the potential to be used as an alternative source of open learning during a pandemic because of its characteristics that support efforts to prevent Covid-19 transmission. Given the potential of DOAJ as an alternative to OER during the pandemic, the use of DOAJ as an alternative to OER can continue to grow after the pandemic period. Therefore, further studies regarding the level of use of DOAJ as an alternative to OER or the level of DOAJ compliance with user information needs will be an interesting study to be investigated in future studies.